QUALIFICATION WORK OF STUDENTS OF HISTORICAL OF THE FACULTY OF THE PEDAGOGICAL UNIVERSITY: MODERN APPROACHES TO IMPLEMENTATION - L.V. Zadorozhna (Academy of Cognitive and Natural Sciences, 2008)
The article deals with the specific character of complex qualification project made by History faculty students of pedagogical university.